2015
DOI: 10.3892/or.2015.4212
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor 19 is correlated with an unfavorable prognosis and promotes progression by activating fibroblast growth factor receptor 4 in advanced-stage serous ovarian cancer

Abstract: Fibroblast growth factor receptor 4 (FGFR4) has been confirmed to be associated with the progression and prognosis of ovarian cancer, while the underlying mechanism has not been well elucidated and the clinical significance of its ligand, fibroblast growth factor 19 (FGF19), has not been explored. To study the clinical significance of FGF19 in advanced‑stage serous ovarian cancer, we detected the expression of FGF19 and FGFR4 by immunohistochemistry (IHC), evaluated the correlation between FGF19 and clinicopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 34 publications
0
10
1
Order By: Relevance
“…Tiong et al suggested that FGF19 and FGFR4 signaling mediated the viability of cancer cells through activation of the PI3K/AKT pathway in breast cancer [ 29 ]. Hu et al also suggested that patients with high expression of both FGF19 and FGFR4 had significantly poor prognoses for ovarian cancer and that FGF19 and FGFR4 signaling could promote ovarian cancer proliferation and invasion through the AKT-MAPK signaling pathway [ 30 ]. In prostate cancer, FGF19/FGFR signaling promotes cancer progression along with the presence of KLa and/or KLb as co-factors [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tiong et al suggested that FGF19 and FGFR4 signaling mediated the viability of cancer cells through activation of the PI3K/AKT pathway in breast cancer [ 29 ]. Hu et al also suggested that patients with high expression of both FGF19 and FGFR4 had significantly poor prognoses for ovarian cancer and that FGF19 and FGFR4 signaling could promote ovarian cancer proliferation and invasion through the AKT-MAPK signaling pathway [ 30 ]. In prostate cancer, FGF19/FGFR signaling promotes cancer progression along with the presence of KLa and/or KLb as co-factors [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…High expression of FGF19 predicts unfavorable prognosis of advanced-stage serous ovarian cancer (357). In vitro, FGF19 promotes ovarian cancer cell proliferation and invasion by activating the FGFR4/Akt-MAPK signaling pathway (357).…”
Section: Reproductive Tissues Cancersmentioning
confidence: 99%
“…Many such alterations have involved tyrosine kinase receptors 4 , which have proven therapeutic potential in a variety of cancer types. One such tyrosine kinase receptor is FGFR4, which has been associated with prognosis in several types of cancer, including lung cancer 5 7 . Several molecular alterations of FGFR4 leading to different gene variants have been identified 8 .…”
Section: Introductionmentioning
confidence: 99%